This too shall last : finding grace when suffering lingers - Ramsey, K. J. (Zondervan, 2020)
Our culture treats suffering like a problem to fix, a blight to hide, or the sad start of a transformation story. We silently, secretly wither under the pressure of living as though suffering is a predicament we can avoid or annihilate by working hard enough or having enough faith. When your prayers for healing haven't been answered, the fog of depression isn't lifting, your marriage is ending in divorce, or grief won't go away, it's easy to feel you've failed God and, worse, he's failed you. If God loves us, why does he allow us to hurt? Through personal story and insights from neuroscience and theology, Ramsey invites us to let our tears become lenses of the wonder that before God ever rescues us, he stands in solidarity with us. We are all mid-story in circumstances we did not choose, wondering when our hard things will end and where grace will come if they don't. We don't need to make suffering a before-and-after story. Together we can encounter the grace that enters the middle of our stories, where living with suffering that lingers means receiving God's presence that lasts.